Rural Ageing as a Negative Factor in the Maghreb and its Effects on Agrarian Productivity” - Machín, Nieva; Pardo, Eric (UNISCI Discussion Papers, 2014)
This article deals with two factors affecting agriculture in three Maghreb countries, Morocco, Algeria and Tunisia: rural ageing and structural deficiencies in the agriculture sector, which will arguably worsen in the future and which have a strong influence on young populations for migrating to the urban milieu in search for better opportunities. We will first review current tendencies in the process of ageing in these countries to conclude that most of the rural ageing finds its roots in migration into the cities. After that, we will deal with the structural deficiencies which are mainly related to lack of institutional support, to the low level of skill in current farmers and to the underdevelopment of infrastructures, not forgetting to mention climate change and the related process of desertification. We will conclude that these two factors feedback each other, being the fact that whenever both phenomena deepen, it will be more difficult to favourably change the situation, as structural deficiencies reduce opportunities for young potential farmers who will then immigrate and leave behind an aged population unfit for introducing improvements in agriculture, and reproducing then the process of emigration. The consequence of this vicious circle will be both reduced productivity and food security.
Keywords: Ageing; Demographics; Emigration; Productivity; Food Security.